PERAN KELOMPOK USAHA WISATA DALAM PENYEDIAAN FASILTAS WISATA DI DESA COLO, KABUPATEN KUDUS - Puspasari, Deny Aditya (JURNAL LITBANG PROVINSI JAWA TENGAH, 2021)
The tourism is one of economic sector, which plays an important role to reduce poverty in a region. Tourism infrastructure become the supporting factors in tourism development, so that the tourism activities can run well. The location of Colo tourim village is in the Muria Mountains, which is the one of potential tourist destinations. Regarding to this potency, the community manages tourism objects independently and informally, such as motorcycle taxis, lodging entrepreneurs, and street vendors. The purpose of this study is to identify the role of these business groups in providing facilities and infrastructure to support tourism activities in Colo Village. The Datas were obtained from the Kudus Regency government institution, and also interviews with the tourism group actors. The results of this study shows that the The tourism groups has a very important role in providing the facilities for tourism activities, so that the tourists will be encouraged to come to the tours provided in Colo Village